1869-1870 Tenn. Pub. Acts 55, ch. 41, § 2 - (:unkn) unknown (My University, 1870)
Prohibited the carry of dirks, sword-canes, Spanish stilletos, belt pistols, pocket pistols, or revolvers. Violators fined not less than ten but no more than fifty dollars and imprisoned not less than thirty days but no more than six months. One thousand dollar bond required to "keep the peace" for six months post-conviction.
Keywords: CARRY